Statin Treatment in the Acute Phase and the Risk of Post-stroke Pneumonia: A Retrospective Cohort Study - Li, Changling; Ma, Mengmeng; Dong, Shuju; Hong, Ye; Bao, Jiajia; Zhang, Yang; Gao, Lijie; Cui, Chaohua; Guo, Jian; He, Li (Frontiers in Neurology, 2021)
Background: We aimed to investigate the impact of statin treatment in the acute phase on the risk and severity of post-stroke pneumonia because of its uncertain effect on post-stroke pneumonia. Methods: Consecutive cases of acute ischemic stroke (AIS) between January 2014 and February 2019 were retrospectively analyzed. We used propensity score matching to adjust for differences in baseline data of the two groups. Additionally, the association of statin treatment in the acute phase with the risk and severity of post-stroke pneumonia was estimated with logistic regression. We registered the present study in Chinese Clinical Trial Registry (ChiCTR 2000032838). Results: Of the 1258 enrolled patients, no significant difference was observed in post-stroke pneumonia risk between the two groups (with / without statin treatment in the acute phase) after propensity score matching (35.1% vs. 27.9%, P = 0.155). We did not find that statin in the acute phase significantly increased the post-stroke pneumonia risk both before and after matched analysis (odds ratio [OR] 1.51, 95% confidence interval [CI] 0.85-2.67, P = 0.157; OR 1.57, 95% CI 0.77-3.18, P = 0.213; respectively). In the 271 patients with post-stroke pneumonia, no significant difference was found in its severity between two groups (19.6% vs. 19.4%, P = 0.964). No significant association was found between statin treatment and post-stroke pneumonia severity (OR 0.95, 95% CI 0.39-2.31, P=0.918). Conclusions: There appeared to be no additional beneﬁts of statin treatment in the acute phase for post-stroke pneumonia reduction among AIS patients.